The First Probable Case of Leprosy in Southeast Italy (13th-14th Centuries AD, Montecorvino, Puglia). (15th July 2012) - Rubini, Mauro; Dell'Anno, Valentina; Giuliani, Roberta; Favia, Pasquale; Zaio, Paola
Abstract : In 2008, during an archaeological excavation on the medieval site of Montecorvino (Foggia, Puglia, Italy), ten individuals were found buried near the principal church. The tombs were dated to the 13th-14th centuries AD, except for one attributable to the 11th century AD. The individual from tomb MCV2 shows some bone changes in the rhinomaxillary area. The most probable diagnosis is that she suffered from a type of near-multibacillary leprosy. Although leprosy has been documented in Italy from the first millennium BC and well described in the first millennium AD, its presence seems to be confined to Northern and Central Italy. This is the first case of leprosy in southeastern Italy and the second in Southern Italy overall. At the moment, the interesting datum is that leprosy seems to appear in Southern Italy only after the first millennium AD. All this could be because of the First Crusade with the opening of new trade and pilgrimage routes to the Near East or simply because other cases of leprosy have still not been found in osteoarchaeological context.